Oxidative Stress-Mediated Aging during the Fetal and Perinatal Periods. (18th August 2014) - Marseglia, Lucia; D'Angelo, Gabriella; Manti, Sara; Arrigo, Teresa; Barberi, Ignazio; Reiter, Russel J.; Gitto, Eloisa
Abstract : Oxidative stress is worldwide recognized as a fundamental component of the aging, a process that begins before birth. There is a critical balance between free radical generation and antioxidant defenses. Oxidative stress is caused by an imbalance between the production of free radicals and the ability of antioxidant system to detoxify them. Oxidative stress can occur early in pregnancy and continue in the postnatal period; this damage is implicated in the pathophysiology of pregnancy-related disorders, including recurrent pregnancy loss, preeclampsia and preterm premature rupture of membranes. Moreover, diseases of the neonatal period such as bronchopulmonary dysplasia, retinopathy of prematurity, necrotizing enterocolitis, and periventricular leukomalacia are related to free radical damage. The specific contribution of oxidative stress to the pathogenesis and progression of these neonatal diseases is only partially understood. This review summarizes what is known about the role of oxidative stress in pregnancy and in the pathogenesis of common disorders of the newborn, as a component of the early aging process.